Cenário de prática em saúde : estudo da preceptoria do pet-saúde na estratégia saúde da família na região metropolitana de Fortaleza - Saldanha, Kátia de Góis Holanda (2015)
In recent decades, the Primary Health Care (ABS) has become a particularly important issue, resulting in the reformulation of different national health systems. The basic field has become a potential and necessary practice space, in which the various health professionals training courses shall insert its students. In this context, the inter-ministerial program PET-Health (Education Program for Working for Health) greatly contributes to the university-service integration. The Preceptor is the figure inserted into the Pet-health that arises in practical scenario, such as health educator professional who provides the student environments that allow them to build and deconstruct knowledge and experiment practical experiences of humanized care. This study investigated the PET-health preceptorship in Family Health Strategy in the municipalities of Fortaleza, Pacatuba and Maracanaú, having as target 82 preceptors professionals of the Family Health Strategy (FHS) in the city of Fortaleza, 12 from Maracanaú and 06 from Pacatuba. Regarding the scholarship students will be surveyed a sample of 113 students from Fortaleza, 24 students and 12 students from Maracanaú and Pacatuba. It is a quantitative and qualitative, descriptive, observational and cross-sectional study. Data collection wasconducted through semi-structured questionnaire directed to students and preceptors. The study was approved by the Research Ethics Committee opinion nº 751 292. It sought to identify and correlate perceptions of competence required on preceptorship according to the preceptors and students, the main difficulties for exercise and what practical results preceptorship in Strategy Family Health brought to preceptors, students and service. Research has shown that 54.43% of the preceptors made a graduate course after the initiation of preceptorship and 65.82% said preceptorship influenced in the choice of course. The results showed the following difficulties in preceptorship: the pedagogical unpreparedness of preceptors, poor infrastructure and little appreciation of preceptorship by the service. With the results it can be concluded that the exercise of PET-health preceptorship is an experience that offers growth possibilities for professional and challenges relative to better preparation of preceptors and services that must be overcome with greater interaction among managers, preceptors, service professionals, educational institutions and community.